(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The text includes a critical analysis of the work of Biancoshock, an artivist from Milan who has operated in the public space since 2004, and an interview which focuses on the peculiarities of his creative multidisciplinary practice. Father of the non-movement Ephemeralism, the artist develops his research under the sign of the temporary action of reappropriation in public space, in which the use of digital media, both critical instrument and object of critique itself, has original aesthetic-conceptual implications, materializing an unedited relationship between real space and virtual space and perpetuating the ephemeral sign over and over. From installations to online performances, or to urban-hacking actions, often carried out in collaboration with other artists both in Italy and abroad, Biancoshock emphasizes how in a hyperconnected society the URL dimension can be really invasive and devastating for the IRL world (=In Real Life), but also how, by embracing a different use of technologies, the former can be an extension to support the latter.